The Implementation of School-Based Management (SBM) in Improving Educational Quality at UPT Satuan Pendidikan SDN Warungdowo I - Hutri Ika Atmawati; Taufiq Harris; A. Faizin (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to describe the implementation of School-Based Management (SBM) in improving the quality of education at SDN Warungdowo I. This research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and documentation. The research informants included the principal, teachers, educational staff, and members of the school committee. The findings indicate that the implementation of SBM is carried out through the principles of autonomy, participation, transparency, and accountability. The application of SBM has a positive impact on improving the quality of learning and strengthening the school’s quality culture. This study provides empirical contributions regarding the practice of SBM implementation in public elementary schools within a local context.